2143. Contact Investigation after Exposure to Active Pulmonary Tuberculosis in the Pediatric Cancer Center. (15th December 2022) - Yoon, Yoonsun; Choi, Joon-sik; Yoon, Hanpum; Cho, Sun Young; Kim, Yae-Jean
Abstract: Background: The prevalence of tuberculosis (TB) in Korean children has decreased due to universal BCG vaccination and the national TB elimination project. However, exposure to TB in children has been consistently reported. There have been few reports of TB exposure in the pediatric hematology-oncology ward. Methods: A mother of a pediatric cancer patient was diagnosed with active TB with a cavity. Contact investigation was performed on patients, their parents, and healthcare workers who were exposed to the index case. The criteria for close contact were exposure in the same space with the index patient for more than 8 hours continuously or a total of 40 hours in case of multiple exposures. The initial assessment was performed as soon as the index case was identified. The second evaluation was conducted 8–10 weeks after the initial exposure. Both tuberculin skin test (TST), TB Specific Interferon-Gamma (T-SPOT) tests, and chest radiography were used in immunocompromised pediatric patients. For immunocompetent adults, the QuantiFERON-TB Gold (QFT-G) test and chest radiography were performed. Results: Total 23 patients and 29 parents were exposed. The median exposure duration of patients was 3 days (1–8 days). The initial evaluation did not detect TB infection in pediatric patients. However, at the second evaluation, five patients (17.4%) were diagnosed with latent TB infection (LTBI, three with positive TST and two with positive T-SPOT), and two patients (8.7 %) were diagnosed with active TB infection (lymphadenitis and pulmonary TB). Among the 29 parents, 11 individuals (37.9%) were diagnosed with LTBI at the initial evaluation, which was considered as preexisting LTBI before this exposure. No additional case of TB infection was identified in the second evaluation. Among exposed 24 healthcare workers, two (9.1%) were eventually confirmed as newly diagnosed LTBI. Conclusion: TB exposure in pediatric hematology-oncology ward and outpatient chemotherapy clinic caused active TB or LTBI cases with an attack rate of 26% in children. The high LTBI rate, up to 38% among parents even before this exposure, needs further intervention such as routine LTBI evaluation and treatment for families of pediatric cancer patients to prevent a similar event. Disclosures: Joon-sik Choi, MD, MS, Ministry of Trade, industry and Energy, Republic of Korea: Grant/Research Support Yae-Jean Kim, MD, PhD, Janssen: Grant/Research Support|Korean Society of Pediatric Infectious Diseases: Grant/Research Support|Ministry of Trade, Industry and Energy: Grant/Research Support|MSD: Grant/Research Support.